2013
DOI: 10.1111/bjd.12140
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical parameters associated with mutational status in metastatic malignant melanoma: a single-centre investigation of 141 patients

Abstract: Mutations of the BRAF gene are correlated with younger age, a higher number of melanocytic naevi and a tumour location in intermittently UV-exposed skin. Signs of chronic photodamage are not indicative of mutational status. Patients with metastatic melanoma with BRAF mutations showed a nonsignificant tendency to progress later to stage IV disease, but once metastases were present the prognosis was identical to that with BRAF wild-type tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
(156 reference statements)
2
14
0
5
Order By: Relevance
“…We observed a correlation between BRAF mutations and being young at the time of primary melanoma diagnosis and an young age at diagnosis of the first metastasis, correlations previously reported [15][16][17][18][19] not confirmed in the meta-analysis by Lee et al 3 The high prevalence of BRAF mutations in young patients (median ages of 57 and 54 years in the retrospective and prospective cohorts respectively) may be linked to BRAF's role as 'strong' oncogenic driver, role attested by its presence in 80% of nevi, 20 meaning that fewer successive mutational events over a shorter time period are in such lesions required for the formation of a melanoma. This correlation currently appears to be specific to melanoma.…”
Section: Discussionsupporting
confidence: 82%
“…We observed a correlation between BRAF mutations and being young at the time of primary melanoma diagnosis and an young age at diagnosis of the first metastasis, correlations previously reported [15][16][17][18][19] not confirmed in the meta-analysis by Lee et al 3 The high prevalence of BRAF mutations in young patients (median ages of 57 and 54 years in the retrospective and prospective cohorts respectively) may be linked to BRAF's role as 'strong' oncogenic driver, role attested by its presence in 80% of nevi, 20 meaning that fewer successive mutational events over a shorter time period are in such lesions required for the formation of a melanoma. This correlation currently appears to be specific to melanoma.…”
Section: Discussionsupporting
confidence: 82%
“…We also showed high interobserver agreement for scoring of the VE1 antibody staining, similar to Marin et al We showed the utility of VE1 on a variety of metastatic and primary melanomas, including different primary melanoma histologic subtypes and metastases from a variety of cutaneous, lymph node, and visceral locations. Furthermore, the VE1 immunostain was associated with younger patient age at diagnosis of the primary melanoma, supporting the association of BRAF mutated melanoma and younger age …”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, the VE1 immunostain was associated with younger patient age at diagnosis of the primary melanoma, supporting the association of BRAF mutated melanoma and younger age. 27 There are several differences in our methods as compared to most previous investigators. These include the use of the Mixed Red Refine reagent from Leica Microsystems as opposed to the Ventana OptiView and Ultraview Universal DAB Detection kits.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, it is not surprising that available data on this topic are inconsistent but suggest a possible adverse prognostic effect for tumors harboring BRAF mutations, whether localized primary tumors, 20 regionally metastatic cases 21,22 or distant metastases are considered. [23][24][25] Further research on the topic is clearly warranted, ideally in the setting of prospective evaluations. At present, it seems premature to base decisions about prognosis solely based on BRAF mutation status.…”
Section: Prognostic Significance Of Braf Mutation In Metastatic Melanomamentioning
confidence: 99%